Silver oxide nanoparticles-decorated tantala nanotubes for enhanced antibacterial activity and osseointegration of Ti6Al4V. (15th September 2018) - Sarraf, Masoud; Dabbagh, Ali; Abdul Razak, Bushroa; Nasiri-Tabrizi, Bahman; Hosseini, Hamid Reza Madaah; Saber-Samandari, Saeed; Abu Kasim, Noor Hayaty; Yean, Lum Kah; Sukiman, Nazatul Liana
Abstract: A long-term antibacterial activity of implants without compromising their biocompatibility is highly desirable to minimize the biomaterial-associated infections. Although tantalum oxide nanotubes (Ta2 O5 NTs) are promising coating materials for orthodontics and orthopedics applications, their insufficient antibacterial activity retains vulnerability to post-implantation infections. This study aimed to endow antibacterial characteristics to the Ta2 O5 NTs-coated Ti6Al4V substrates by decoration of silver oxide nanoparticles (Ag2 O NPs). The well-adherent Ta2 O5 NTs were grown via anodization of a pure tantalum (Ta) layer coated by physical vapor deposition (PVD) on the Ti6Al4V substrates. The Ag2 O NPs were then decorated on the edges and walls of nanotubes through a secondary PVD under controlled conditions. The silver oxide nanoparticles-decorated tantala nanotubes (Ag2 O NPs-decorated Ta2 O5 NTs) promoted the formation of bone-like apatite layer and significantly reduced the viability of Escherichia coli ( E. coli ) cells. The prepared coating also increased the density and spreading of osteoblast cells in comparison to bare substrate. These results suggest that decorating the Ta2 O5 NTs with Ag2 O nanoparticles could improve antibacterial activity and the osseointegration of Ti6Al4V implants. Graphical abstract: Unlabelled Image Highlights: Ag2 O nanoparticles were decorated on the edges of Ta2 O5 nanotubes through a controlled physical vapor deposition procedure. The coating promoted formation of a bone-like apatite layer with Ca/P of 1.61 after soaking in SBF for 14 days. An effective antibacterial activity was seen against Escherichia coli via membrane disruption and intracellular leakage. Morphological and viability studies indicated a significant proliferation of human osteoblasts during the culture time.